ANALISIS PERBEDAAN INFORMASI ANATOMI PADA PEMERIKSAAN CT SCAN ABDOMEN ANTARA PENGGUNAAN PROTOKOL SURE EXPOSURE DAN TANPA SURE EXPOSURE - Devita Rizkania Indarsari; Jeffry Ardiyanto; Andrey Nino Kurniawan (Poltekkes Kemenkes Semarang, 2019)
Background : Image quality Abdomen CT scan is said to be either indicated by low noise or image noise values within acceptable standard limits. One of the parameters affecting image noise is mAs. On CT Scan aircraft there is an auto mAs setting facility called Sure exposure to ensure constant image quality at the lowest possible dose. The purpose of this study was to determine the difference of anatomical information to the use of sure exposure protocol and without sure exposure on CT scan of Abdomen and to know better protocols in producing quality on CT Scan Abdomen between usage protocol sure exposure and without sure exposure.Method : This research is a kind of quantitative research with experimental approach. This study used the CT Scan Multislice 128 plane on CT scan of Abdomen with the use of sure exposure protocol and without sure exposure. The results were obtained based on respondents assessment through Liver, Spleen, Adrenal Gland, Kidney, Pancreas and Abdominal Wall. Analyze this research data using statistical test.Result : The results of the questionnaires of respondents on liver, spleen, adrenal gland, kidney, pancreas and abdominal wall showed no significant difference. This is followed by the value of Mann Whitney's overall significance of the abdominal anatomy is 0.549 (p value 0.05). Protocol Sure Exposure is better on the organ of adrenal glands, kidneys and pancreas, whereas protocols without sure exposure are better in liver, spleen, kidney, pancreas, and abdominal wall. The use of protocols without sure exposure better in generating information.Conclusion : In general the protocol of sure exposure and without sure exposure has the same clarity of anatomical information. But the protocol without a sure exposure has more information than the sure exposure protocol.